Reverse sural artery flap for posterior ankle soft tissue defect - Abdelaziz M. Ali (Al-Azhar Assiut Medical Journal)
Background and aim Soft tissue defects of the ankle provide a significant challenge to reconstructive surgeons. Several techniques have been documented for this reconstruction, and all of these techniques varied in cost, difficulty, and outcomes. This study aims to evaluate the reverse sural artery flap for posterior-ankle soft tissue defect reconstruction. Patients and methods Nine patients with posterior ankle soft tissue defects due to different etiologies and requiring reconstruction were included and operated in the reconstructive microsurgery unit of Al-Azhar University Hospital, Assiut, Egypt, during the period between 2019 and 2022. These defects were covered by the reverse sural artery flaps. The follow-up period ranged from 18 to 36 months, and all the patients were evaluated for functional outcomes in terms of ulceration, sensation, patient satisfaction, and complications. Results All flaps survived with no complications. The mean operative time was 1.4±0.33 h. (1–2 h) and the mean hospital stay period was 2.4±0.52 days. Postoperatively, ulceration was recorded in 2 (22.2%) cases and sensation in all cases and the majority of patients were satisfied with the results (8 cases, 88.9%). Five cases had good Maryland score (55.6%), 2 (22.2%) cases had excellent, and only 1 case was recorded for poor and fair scores. All the defects were covered effectively with no complications. Conclusion The reverse sural artery flap could be one of the effective treatment methods for reconstructing posterior-ankle soft tissue defects. Besides, it has high reliability, ease, and versatility.